Identità e relazioni femminili nel paese di approdo. Le donne bangladesi musulmane a Roma - Carnà, Katiuscia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The research has set itself the objective of analysing and deepening the social capital and subsidiarity relationships of Bangladeshi women in Rome in relation also with the indigenous community. The survey took place from 2014 to 2017. The methodology used is qualitative type through participatory observation and twenty semistructured interviews with Bangladeshi women aged (19-42 years) and different social status. The research aimed to understand the various socio-demographic variables that characterize and de-limit the inclusion of Muslim Bangladeshi women in Rome and social interaction with the indigenous community, in the ambivalent affirmation of identity between women, tradition, migration and religion, in a sort of cultural and generational collision with the new generations.